The Effectiveness of the Integrated Islamic LKPD Bangun Flat Based on the Linktree Digital Platform to Facilitate Religious Literacy of Mts Students - Maulidani, Muhammad; Masamah, Ulfa (Proceeding International Conference on Religion, Science and Education, 2024)
This research aims to determine the level of effectiveness of the Student Worksheet (LKPD) based on the Linktree digital platform on the subject of flat figures and to find out whether the LKPD can facilitate the religious literacy of MTs students. This research is development research ( Research and Development ) by adopting the 4D procedure with the stages of Define , Design , Development , and Dissemination . At the development stage, a process of validity testing and practicality testing is carried out. The trial was carried out in class VIII Girls at MTs Sabilurrosyad Malang using a research trial using a research instrument on the effectiveness of using LKPD sheets. The results of the development research show that the Islamic Integrated Bangun Datar LKPD based on the Linktree digital platform is included in the very valid category as seen from the results of the validity test: (1) From the validation results, media experts obtained an average score of 96.61 with very valid criteria ; (2) Validation by material experts received an average score of 97.34 with very valid criteria; (3) Validation by integration experts obtained an average score of 96.87 with very valid criteria. In the development process, an analysis of the religious literacy of MTs students was also carried out. This analysis was carried out using a religious literacy questionnaire. The results of the questionnaire test showed results with a score of 78.81 so that the LKPd can facilitate students' religious literacy.